Study on association of nuclear factor kappa B gene polymorphism with bacterial load in pulmonary tuberculosis - Pallavi Baliarsingh; Pratima Kumari Sahu; Paresh Nath Mohanty; Roma Rattan; Monalisa Mohapatro (The Journal of Association of Chest Physicians)
Objectives: Pulmonary tuberculosis (PTB) is a leading infectious disease and a major public health concern. Out of susceptible genes, nuclear factor kappa B (NF-κB) gene influences inflammation and hence the progression of the disease. A single nucleotide polymorphism of functional NF-κB1 promoter −94 ins/del ATTG (rs28362491) has a regulatory effect on the NF-κB1 gene. The aim of our study was to ascertain the bacterial load and to find the association with NF-κB gene polymorphism. Methodology: One hundred two diagnosed and microbiologically confirmed cases of PTB patients between 18 and 69 years of age and 102 healthy age, sex, and socioeconomic status–matched volunteers were taken as controls. Sputum from cases and blood samples from cases and controls were collected. Bacterial load estimation was done from the sputum sample. Genomic deoxyribonucleic acid (DNA) was extracted for NF-κB gene. Polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) were performed. Results: The genotypic frequency of ins/del was found to be 54.9% in PTB patients which was more than that of the other genotype frequencies in the case group and also from the control genotype frequencies, although it was found to be insignificant (P value = 0.098). On analysis of bacterial load with NF-κB gene polymorphism, a significant association was found more particularly for ins/del versus del/del. Conclusion: The bacterial load showed significant variation among the del/del genotype, ins/del genotype, and ins/ins genotype which was statistically significant. The del/del genotype exhibited the highest bacterial load in and greater statistical significance was found between ins/del and del/del genotypes. This implies the association between NF-κB gene polymorphism and bacterial load.